INHOMOGENEITIES IN THE ATTENUATION FIELD OF SHORT-PERIOD S-WAVES IN THE SOURCE ZONE OF THE ASSAM EARTHQUAKE ON AUGUST 15, 1950 - Kopnichev Y.F.; Gordienko D.D.; Sokolova I.N. (My University, 2007)
Characteristics of the attenuation field for S-waves are studied in the uppermost mantle in the source zone of the Assam earthquake. The method of study is based on the analysis of envelopes of the short-period coda for Lg and Sn waves. It was found that attenuation in the uppermost mantle regularly increases from the central part of the source zone to its periphery and further at distances up to 200 km from the aftershock region. In general, the attenuation in the source zone is significantly weaker than in many regions, where no strong earthquakes have occurred in the last 100 yr with M ≥ 6.5. The obtained data evidence that mantle fluids ascend to the Earth’s crust in the source zone, probably due to a sharp increase in the permeability of the rocks provoked by the strongest earthquake.